2004
DOI: 10.1262/jrd.50.361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Uterine Inflammation on the Estrous Cycle in Rats

Abstract: Abstract. To investigate how uterine inflammation affects ovarian activity in rats, endometritis was induced and changes in the length of estrous cycle and serum concentrations of estradiol-17β (E2) and progesterone (P4) were examined. A suspension of Staphylococcus aureus (bacterial solution) or iodine solution was infused into the uterine lumen at various estrous phases. When the bacterial solution was infused at estrus, metestrus, or the first day of diestrus, the following diestrus continued for 5 to 12 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…PR/actin values were normalized between blots (see Methods) statistical differences determined by two-way ANOVA and expressed as group mean ± SEM (Fig. 4b), consistent with previous reports demonstrating lowest uterine weights occurring in diestrus rats and the suppressive effects of inflammatory stressors on the estrous cycle [25,26]. The remaining 3/10 intact rats infused with LPS were in early proestrus (1/10) and metestrus (2/10), both stages characterized by the presence of leukocytes.…”
Section: Brain Infusion Of Lps Suppressed Uterine Weight In Intact Ratssupporting
confidence: 73%
See 2 more Smart Citations
“…PR/actin values were normalized between blots (see Methods) statistical differences determined by two-way ANOVA and expressed as group mean ± SEM (Fig. 4b), consistent with previous reports demonstrating lowest uterine weights occurring in diestrus rats and the suppressive effects of inflammatory stressors on the estrous cycle [25,26]. The remaining 3/10 intact rats infused with LPS were in early proestrus (1/10) and metestrus (2/10), both stages characterized by the presence of leukocytes.…”
Section: Brain Infusion Of Lps Suppressed Uterine Weight In Intact Ratssupporting
confidence: 73%
“…Consistent with these findings, most intact LPS-infused rats were in diestrus after 8 weeks and had reduced uterine weight that correlated to activated microglia in the brain. While others have documented uterine effects within 2 weeks of inflammatory stressor initiation [25,26], we report that these physiological changes can persist weeks after cessation of LPS infusion. These data highlight the long-term impact of inflammatory stress on reproductive function.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Together, these studies suggest that relatively high concentrations of progesterone (0.1 to 3 μM) can affect myocardial function at the cellular level. However, these studies have all utilized relatively high concentrations of the hormone; circulating levels of progesterone range from 1 to 64 nM in premenopausal women [30] and between 3 and 55 nM in rodents [60, 121]. Whether lower concentrations of progesterone affect the contractile function of cardiomyocytes in vitro should be further examined.…”
Section: The Impact Of Sex Steroid Hormones On Cardiac Ec Coupling Mementioning
confidence: 99%
“…Xiao et al [16] also reported that IL-1 stimulated P 4 secretion from the adrenals in the ovariectomized rhesus monkey; therefore, the P 4 concentration rise observed in OvxBac on day 4 might have been due to these mechanisms. Kaneko et al [4] reported that bacterial inoculation into the uterus of rats prolonged anestrus to 9.3 days from the original 2 days, and they concluded that the P 4 , which was increased in blood after bacterial inoculation, was the main reason for the extension of anestrus. Our results support their theory since the P 4 concentration increased in all the treatment groups.…”
Section: Discussionmentioning
confidence: 99%